2008
DOI: 10.1097/mot.0b013e3283186b51
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile infection in solid organ transplant recipients

Abstract: C. difficile is a significant pathogen in solid organ transplant recipients. Multiple risk factors are found in this population that may result in more severe disease. A high index of suspicion is necessary for the early diagnosis and treatment of C. difficile infection in transplant recipients. Metronidazole and vancomycin show equivalent efficacy in the treatment for mild-to-moderate disease, but vancomycin has demonstrated superiority in the treatment of severe disease. Surgical intervention is also an impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 136 publications
3
74
0
2
Order By: Relevance
“…Nevertheless, in transplant recipients with diarrhea, CDAC should always be very high in the suspected diagnoses. A recent report suggested that SOT recipients may not be at high risk for relapsing CDAC; however, others have found the opposite [1,3,10,11].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Nevertheless, in transplant recipients with diarrhea, CDAC should always be very high in the suspected diagnoses. A recent report suggested that SOT recipients may not be at high risk for relapsing CDAC; however, others have found the opposite [1,3,10,11].…”
Section: Introductionmentioning
confidence: 93%
“…A growing number of reports have emphasized that solid organ transplant (SOT) recipients carry a high risk to develop Clostridium difficile-associated colitis (CDAC) [1][2][3][4][5][6][7][8][9][10][11]. Moreover, the course of the disease seems to be more severe in this patient population [1,4,6,10].…”
Section: Introductionmentioning
confidence: 99%
“…Aunque la administraci贸n antimicrobiana previa se ha demostrado en m谩s de 95% de los pacientes inmunocompetentes con ICD, esta asociaci贸n se reduce a 80% en receptores de trasplante de 贸rgano s贸lido. La reducci贸n en la relaci贸n con exposici贸n antimicrobiana puede ser secundaria a alteraciones en la microbiota normal y al deterioro de la inmunidad debido a inmunosupresores, enfermedad pre-trasplante grave e intervenci贸n quir煤rgica 34,35 . La disfunci贸n del sistema inmune es tambi茅n un importan-te factor de riesgo en pacientes receptores de trasplante de 贸rgano s贸lido.…”
Section: Poblaciones Especialesunclassified
“…Immunocompromised patients may represent a special subset of CDI for which the incidence and treatment may be more challenging to approach, in particular those with solid organ transplantation. The incidence of CDI in transplant patients has been estimated at 3%-7% for liver recipients, 3.5%-16% for kidney recipients, 1.5%-7.8% in pancreas-kidney recipients, 9% in intestinal recipients, 15% in heart recipients, and 7%-31% in lung recipients [16] . Further fulminant colitis is noted to occur in up to 8% of immunocompromised patients and 13% of solid organ transplant recipients with the highest incidence within the first 3 mo [17,18] .…”
Section: Risk Factors For CDImentioning
confidence: 99%
“…In a prospective study of diarrheal pathogens, 20% of infections were community acquired. For an additional 15% of patients, CDI was acquired in the hospital, but diarrhea began after discharge at home for a total of 43% of cases with onset of symptoms at home [16] . As many as 25% of all cases of CDI develop in nursing home patients [1] .…”
Section: Risk Factors For CDImentioning
confidence: 99%